Ovarian Endometriomas Infertility and in Vitro Fertilization: Review of the Literature - Kıran, Hakan; Kaplanoğlu, Mustafa (Gynecology Obstetrics & Reproductive Medicine, 2007)
Endometriosis is one of the most common cause in infertility and most commonly observed in pelvic peritoneum, on the ovaries and uterosacral ligaments. The infertility associated with endometriosis has been attributed to several mechanism such as impaired peritoneal enviroment, distored the pelvic anotomic stracture, reduced endometrial receptivity. Endometrioma is commonly found pathology of endometriosis. Endovaginal ultrasonography is relevant for the diagnosis of ovarian endometriomas with a good predictive value. The treatment of endometriomas are frequently surgical. Several surgical techniques are performed in endometrioma. Operative laparoscopic management is the ‘gold standard’ for surgical treatment. Surgical treatment in infertile women with endometrioma can be restored to normal anatomic stracture. IVF/ICSI treatment can be recommended in this women. On the other hand, the results of this treatment is argumented.